A method for tumor dosimetry based on hybrid planar‐SPECT/CT images and semiautomatic segmentation. Issue 11 (8th October 2018) - Roth, Daniel; Gustafsson, Johan; Sundlöv, Anna; Sjögreen Gleisner, Katarina
Abstract : Purpose: A hybrid planar‐SPECT/CT method for tumor dosimetry in 177 Lu‐DOTATATE therapy, applicable to datasets consisting of multiple conjugate‐view images and one SPECT/CT, is developed and evaluated. Methods: The imaging protocol includes conjugate‐view imaging at 1, 24, 96, and 168 h post infusion (p.i.) and a SPECT/CT acquisition 24 h p.i. The dosimetry method uses the planar images to estimate the shape of the time–activity concentration curve, which is then rescaled to absolute units using the SPECT‐derived activity concentration. The resulting time‐integrated activity concentration coefficient (TIACC) is used to calculate the tumor‐absorbed dose. Semiautomatic segmentation techniques are applied for tumor delineation in both planar and SPECT images, where the planar image segmentation is accomplished using an active‐rays‐based technique. The selection of tumors is done by visual inspection of planar and SPECT images and applying a set of criteria concerning the tumor visibility and possible interference from superimposed activity uptakes in the planar images. Five different strategies for determining values from planar regions of interest (ROIs), based on entire or partial ROIs, and with and without background correction, are evaluated. Evaluation is performed against a SPECT/CT‐based method on data from six patients where sequential conjugate‐view and SPECT/CT imaging have been performed in parallel and against ground truths in Monte Carlo simulated images. The patient data are also used to evaluate the interoperator variability and to assess the validity of the developed criteria for tumor selection. Results: For patient images, the hybrid method produces TIACCs that are on average 6% below those of the SPECT/CT only method, with standard deviations for the relative TIACC differences of 8%–11%. Simulations show that the hybrid and SPECT‐based methods estimate the TIACCs to within approximately 10% for tumors larger than around 10 ml, while for smaller tumors, all methods underestimate the TIACCs due to underestimations of the activity concentrations in the SPECT images. The planar image segmentation has a low operator dependence, with a median Dice similarity coefficient of 0.97 between operators. The adopted criteria for tumor selection manage to discriminate the tumors for which the absorbed‐dose deviations between the hybrid and SPECT methods are the highest. Conclusions: The hybrid method is found suitable for studies of tumor‐absorbed doses in radionuclide therapy, provided that selection criteria regarding the visibility and overlapping activities in the planar images are applied.